A rare case of a congenital anomalous origin of the coronary arteries: All in one - (:unkn) unknown (My University, 2014)
Koroner arterlerin konjenital çıkış anomalisi nadir bir durum olup anjiografi serilerinde insidansı %0,6-1,3 olarak gösterilmiştir. Koroner arter anomalisi olan hastaların çoğunda bulgu olmamasına ragmen, büyük arterlerin koroner arterlere dışarıdan bası oluşturması durumunda yüksek ani kardiyak ölüm riskine sahiptirler. Bu hastaların tedavisinde hala bir fikir birliği bulunmamaktadır. Bu olgu sunumunda, sağ koroner arterin ve sol ana koroner arterin sağ koroner sinuste, tek bir çıkış yolundan köken aldığı nadir bir koroner anomali vakasını sunduk.

Congenital anomalous origin of the coronary arteries is a rare condition with an incidence of 0.6-1.3% in angiographic series.The majority of patients with an anomalous origin of the coronary artery is asymptomatic. They have higher risk of sudden cardiac death if there is external compression of the coronary arteries by the great arteries. There still is not consensus on the management in these patients. In this case report, we present a rare case of a coronary anomaly where both the right coronary artery and the left main coronary artery arise from the right coronary sinus and there is a single ostium.
Nadir bir vaka olarak koroner arterlerin konjenital çıkış anomalisi: Hepsi bir arada
Keywords: Genel ve Dahili Tıp